2007
DOI: 10.1200/jco.2006.09.2940
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Axial Skeleton for Detecting Bone Metastases in Patients With High-Risk Prostate Cancer: Diagnostic and Cost-Effectiveness and Comparison With Current Detection Strategies

Abstract: MRIas is more sensitive than the current SW of radiographically identified bone metastases in high-risk PCa patients, which impacts the clinical management of a significant proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(97 citation statements)
references
References 44 publications
9
83
0
5
Order By: Relevance
“…Bone marrow MRI has been shown to be more sensitive and specific than bone scanning for the detection of bone metastases and to reveal them earlier (74). In a study of 66 patients with high-risk prostate cancer, the sensitivity and specificity of onestep MRI of the axial skeleton (100% and 88%, respectively) were markedly higher than those of bone scanning (46% and 32%, respectively) for detecting bone metastases and changed treatment planning in 22% of patients (75). More research is needed to determine the diagnostic value and cost-effectiveness of one-step MRI in the assessment of bone metastases.…”
Section: Mri In the Pretreatment Detection Of Metastasesmentioning
confidence: 99%
“…Bone marrow MRI has been shown to be more sensitive and specific than bone scanning for the detection of bone metastases and to reveal them earlier (74). In a study of 66 patients with high-risk prostate cancer, the sensitivity and specificity of onestep MRI of the axial skeleton (100% and 88%, respectively) were markedly higher than those of bone scanning (46% and 32%, respectively) for detecting bone metastases and changed treatment planning in 22% of patients (75). More research is needed to determine the diagnostic value and cost-effectiveness of one-step MRI in the assessment of bone metastases.…”
Section: Mri In the Pretreatment Detection Of Metastasesmentioning
confidence: 99%
“…A study of 66 patients with high-risk prostate cancer has shown no cases of isolated peripheral metastases (Lecouvet et al, 2007). With newer scanners, coverage of the whole skeleton with MRI by use of whole-body coil arrays or moving table arrangements is possible but it is time consuming, and the difficulty with MR interpretation of certain areas, such as ribs, does not make such intensive imaging worthwhile.…”
Section: Mri For Assessment Of Bone Metastasesmentioning
confidence: 99%
“…Magnetic resonance has been shown to detect bone metastases in 37.5% of patients with negative or inconclusive bone scan and plain films, and one prospective study indicates sensitivities and specificities of 100 and 88% for MRI and 46 and 32% for bone scintigraphy (Lecouvet et al, 2007). The discrepancy between these modalities arises because even with extensive marrow involvement by metastases, the amount of bony matrix destroyed is small (Taoka et al, 2001).…”
Section: Mri For Assessment Of Bone Metastasesmentioning
confidence: 99%
“…Bone scintigraphy predicts the risk of spinal cord compression, a major cause of morbidity in CRPC [36]. However, scintigraphy may lack sensitivity compared with magnetic resonance imaging (MRI) for early detection of spinal metastases [37].…”
Section: Highlight Clinical Benefitmentioning
confidence: 99%